Rola strategii w kształtowaniu płynności finansowej na przykładzie spółki Elektrim S.A. - Wawryszuk-Misztal, Anna (Strategy's Role in Maintaining Financial Liquidity on the Example of Elektrim SA, 2008)
Making decisions in the area of financial management is connected with the firm's overall strategy. Strategic decisions cannot be made without taking into account financial aspects and conversely, decision made in the area of financial management should take into consideration the firm's strategy. The strategy of Elektrim SA executed between 1998 and 2001 indicates that the relationship between strategy and finance is crucial for maintaining long-term liquidity.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1200, s. 588-596